Thanks for watching : an anthropological study of video sharing on YouTube - Lange, Patricia G. (University Press of Colorado, 2019)
"YouTube hosts one billion visitors monthly and sees more than 400 hours of video uploaded every minute. An anthropological perspective on this mediated social environment, demonstrating how core concepts from anthropology-participant-observation, reciprocity, and community-apply to sociality and how to reconceptualize and update these concepts"--